Resetting population mobility responses under repeated nonpharmaceutical interventions: Implications for hypothesized pandemic fatigue - Albano Rikani; Laura Di Domenico; Chiara E. Sabbatini; Victor Navarro; Leo Ferres; Jocelyn Raude; Vittoria Colizza (Proceedings of the National Academy of Sciences, 2026)
Nonpharmaceutical interventions (NPIs) are essential for controlling infectious diseases during prevaccine periods, yet their success hinges on sustained population behavioral responses to restrictions. This study investigates how mobility responses to tiered restriction systems evolved over time during COVID-19 in six geographical regions across Europe, North America, Africa, and South America. Using daily mobility data and linear-mixed models, we characterized three temporal dimensions shaping these responses: cumulative exposure to restrictions, time spent under a given tier, and repeated reintroduction of the same tier. Time spent under a given tier caused the most rapid attenuation of mobility reduction, producing effects within days that cumulative exposure, required months of restrictions to achieve. Iterative application of shorter NPIs, interspersed with temporary relaxation, was associated with a restoration of mobility responses when restrictions were reintroduced, mitigating attenuation and sometimes even strengthening responses. These patterns are consistent with mechanisms discussed under the umbrella of pandemic fatigue, whereby temporary relaxation may provide psychological relief and a sense of regained autonomy that can renew public willingness to respond to restrictions when reintroduced, while remaining compatible with behavioral adjustment and structural constraints. However, they are also compatible with alternative explanations, including behavioral adaptation, structural constraints on mobility, or evolving interpretations of restrictions. These findings emphasize the dual benefits of short, strategic NPIs for epidemic control and public resilience, offering actionable insights for designing more sustainable pandemic interventions.